Peran Dinas Kearsipan dan Perpustakaan dalam preservasi dan komunikasi kebudayaan lokal Provinsi Jawa Tengah - Roro Isyawati Permata Ganggi; Athanasia Octaviani Puspita Dewi (Perpustakaan Universitas Gadjah Mada, 2021)
Introduction. The purpose of this paper is to explore the role of The Office of Archive and Library in preservation and communication of local culture. Data Collection Method. Using a case study, this paper involved the data collection by interviews, observations and literature review. Data Analysis. The data were descriptively analysed by using thematic analysis. Results and Discussion. The Office of Archive and Library has three roles in preservation and communication of local culture. They are: (1) as an information provider; (2) as a local cultural preservation agency; and (3) as a communicator of local cultural information. The role in preservation and communication of local culture arises because of the duties of the Office of Archive and Library Office in managing knowledge and efforts to fulfill the intellectual needs of the community. Conclusion. Preservation and communication of local culture conducted by the Office of Archive and Library Office is a manifestation of the function of library. The role in the preservation and communication of local culture will continue to develop in accordance with the user needs.